Policy critics and policy survivors: who are they and how do they contribute to a department policy role typology?. Issue 6 (2nd November 2017) - Golding, Jennie
ABSTRACT: This paper considers the policy 'roles' adopted by teachers enacting policy in a department. It draws on a longitudinal study of two secondary mathematics departments endeavouring to make deep change aligned with a demanding curriculum policy. The study validates aspects of an existing typology, demonstrates the existence of a variety of policy 'critics' and adds a category of 'survivor' teacher, showing the role can have considerable impact on enactment. The paper argues for an extension to a group construct of 'policy role', here at a department level, and shows that as teachers struggle to marry the constraints of the range of policies to which they are subject with the time and effort needed to maintain deeply espoused professional values, an adopted group role can serve either to support or constrain individual teacher efforts.